Respuesta :
Answer:
[tex]x=1[/tex]
B
Step-by-step explanation:
So we have the equation:
[tex]3x-x+2=4(2x-1)[/tex]
Combine like terms on the left:
[tex]3x-x+2=4(2x-1)\\2x+2=4(2x-1)[/tex]
Distribute out the right:
[tex]2x+2=4(2x-1)\\2x+2=8x-4[/tex]
Subtract 2x from both sides. The left side cancels:
[tex](2x+2)-2x=(8x-4)-2x\\2=6x-4[/tex]
Add 4 to both sides. The right side cancels:
[tex]2+4=(6x-4)+4\\6=6x[/tex]
Divide each side by 6:
[tex](6)/6=(6x)/6\\x=1[/tex]
Therefore, the solution is: x=1.
X = 1
Porque:
3x - x + 2 = 4(2x - 1)
3x - x + 2 = 8x - 4
3x - x - 8x = - 4 - 2
- 6x = - 6
x = - 6/ -6
x = 1 ✔️
Porque:
3x - x + 2 = 4(2x - 1)
3x - x + 2 = 8x - 4
3x - x - 8x = - 4 - 2
- 6x = - 6
x = - 6/ -6
x = 1 ✔️